Employment Regulations and Creation of Skilled Manpower in Industry in East Java Province - Achmad Room Fitrianto; Andriani Samsuri; Betty Silfia; Aidah Kamaliah; Firdayanti Hadiansyah; Andri Afianto (Jurnal Public Policy, 2022)
The purpose of this study is to further analyze the effect of labor regulations in Indonesia on the provision of skilled labor and encourage entrepreneurs to provide labor in Indonesia to improve export quality. This research uses mixed methods, with a combination of qualitative and quantitative methods to be able to provide results and descriptions related to the influence of labor regulations on workforce creation. This study underscores three important things. First, the understanding of business actors towards labor regulations is still low, and some do not yet know it. Second, the limited capacity of business actors (funds, time, and experts) to conduct intensive and unique training in obtaining skilled workers. Third, the government's attention to labor regulations is still relatively low. So far, the routine is the determination of the UMK every year. Overall, this study observes that no derivative regulations are applied at the local level in creating skilled workers, which causes employers to seek to provide skilled workers with available resources.